(untitled) (Medico Legal Update, 2020)
“A study to assess the knowledge on oral health and self-esteem among young adults in selected college, Kancheepuram district, Tamil Nadu, India’’. The objectives are to assess the knowledge on oral health among college students and to assess the self-esteem among college students and to correlate the knowledge on oral health and self-esteem among college students and to associate the knowledge on oral health and self-esteem with selected demographic variables among college students. The convenience sampling was used to select 100 young adults. The data collection tools were validated and reliability was established. The data was collected from the students in selected college. The collected data was Tabulated and Analysed. The results revealed that Majority of young adults were female 53% and 43% were males. Majority of young adults were in78% got information through mobile phone 9% were got information through newspaper 8% of young adults got information through television and 5% of young adults get information through health professionals. Present study result shows that Mean score of knowledge was 24.58 and mean score of self-esteem was 28.18. There was statistically mild positive correlation was found between the level of knowledge and the level of self-esteem. There is no statistically significant association between selected demographic variables and the level of found knowledge. There is an statistically significant association found between frequency of brushing and frequent rinsing of mouth and level of self-esteem and there is no statistically significant association found between demographic variables.